Accelerated whole‐heart MR angiography using a variable‐density poisson‐disc undersampling pattern and compressed sensing reconstruction. Issue 2 (11th May 2017) - Moghari, Mehdi H.; Uecker, Martin; Roujol, Sébastien; Sabbagh, Majid; Geva, Tal; Powell, Andrew J.
Abstract : Purpose: To accelerate whole‐heart three‐dimension MR angiography (MRA) by using a variable‐density Poisson‐disc undersampling pattern and a compressed sensing (CS) reconstruction algorithm, and compare the results with sensitivity encoding (SENSE). Methods: For whole‐heart MRA, a prospective variable‐density Poisson‐disc k‐space undersampling pattern was developed in which 1–2% of central part of k‐space was fully sampled, and sampling in the remainder decreased exponentially toward the periphery. The undersampled data were then estimated using CS reconstruction. In patients, images using this sequence with an undersampling rate of ≈6 were compared with those using a SENSE rate of 2 (n = 15) and a SENSE rate of 6 (n = 13). Results: Compared with SENSE rate 2, CS rate 6 images had similar objective border sharpness, significantly lower subjective image quality scores at all four locations (all P  < 0.01), and shorter scan times ( P  < 0.05). Compared with SENSE rate 6, CS rate 6 had similar objective border sharpness at all four locations, significantly better subjective image quality scores at three of four locations (all P  < 0.01), and similar scan times ( P  = 0.24). Conclusion: Compared with SENSE with a comparable acceleration rate, a variable‐density Poisson‐disc undersampling pattern and CS reconstruction achieved better subjective image quality and similar border sharpness. Magn Reson Med 79:761–769, 2018. © 2017 International Society for Magnetic Resonance in Medicine.